2014 ASEE Annual Conference &Amp; Exposition Proceedings
DOI: 10.18260/1-2--23116
|View full text |Cite
|
Sign up to set email alerts
|

Text Books: eBooks or Print

Abstract: Electronic books or Ebooks are becoming more and more common in colleges. In this research, the student book buying patterns are studied at a public engineering institution. Ebooks are becoming more and more common. Based on a research survey, we analyze whether students prefer ebooks or print editions. Comparisons are done across disciplines, level of the student (freshman to graduate), whether the student owns a laptop / desktop / tablet, student work commitments, financial needs, and age; among other factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 0 publications
1
6
0
Order By: Relevance
“…If the digital natives narrative were to hold true, then we would perhaps expect more of this generation to prefer digital texts. This preference for printed texts is similar to that seen in research in the social sciences and more general research on reading preferences in adults …”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…If the digital natives narrative were to hold true, then we would perhaps expect more of this generation to prefer digital texts. This preference for printed texts is similar to that seen in research in the social sciences and more general research on reading preferences in adults …”
Section: Resultssupporting
confidence: 81%
“…This preference for printed texts is similar to that seen in research in the social sciences 22 and more general research on reading preferences in adults. 23 All students are introduced to the ebook service by a librarian with a face to face session in a lectures slot, with many completing the sign up process in that session. This means that 84% of the 2018−19 cohort were registered for the ebook; however, only 74% of the registered users (and therefore 65% of the cohort) were considered to be active users (Figure 2).…”
Section: ■ Resultsmentioning
confidence: 99%
“…This innovation, which has the potential to drastically alter traditional reading habits, should be promoted and enhanced. According to Khalid (2014) teachers' degree of expertise and approach to e-book devices may have an impact on how they teach their pupils about e-books. Furthermore, most instructors who have difficulty adjusting to technology devices learn about them at the schools where they work rather than during their university years.…”
Section: The Problems Of E-textbooks In the Classroommentioning
confidence: 99%
“…The pages can be turned and the object can be felt as well as held. Khalid (2014) found that around 85% of his respondent agreed that the majority of texts were still in the form of printed books. The students preferred printed textbooks for a variety of reasons, but readability, use, and mobility were the main ones.…”
Section: Introductionmentioning
confidence: 99%